Delta Opioid Receptor Agonists Ameliorate Colonic Inflammation by Modulating Immune Responses - Nagata, Kazuki; Nagase, Hiroshi; Okuzumi, Ayumi; Nishiyama, Chiharu (Frontiers in Immunology, 2021)
The opioid receptors play important roles in the regulation of sense and emotions. Although it is recently revealed that opioid receptors are also expressed in various cells, but not restricted in the central nervous system, the effects of opioids on peripheral immune cells are largely unknown. In the current study, we evaluated the effect of opioids on immune system by using selective agonists for delta opioid receptor. Systemic administration of KNT-127 or intraperitoneal injection of YNT-2715 (a KNT-127-related compound that cannot pass through the blood-brain barrier) significantly alleviated the pathology of dextran sodium sulfate-induced colitis. In KNT-127-treated mice, the levels of inflammatory cytokine IL-6 in the serum, and macrophages in the mesenteric lymph nodes (MLNs) were decreased in the progression stage, and those of regulatory T cells (Tregs) in the MLN were increased in the recovery stage. In vitro experiments revealed that KNT-127 inhibited the release of IL-6 and another inflammatory cytokine TNF-alpha from macrophages and accelerated the development of Tregs. Our study suggests that delta opioid agonists act directly on immune cells to improve the pathology of the colitis and can be candidates of immunomodulatory drugs.